Chylous ascites following total laparoscopic hysterectomy done for benign pathology: a rare complication - K. S. Raja Rajeswari; Vidhyantha, Kiruba Hannah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Chylous ascites is an uncommon form of ascites, defined as the leakage of the lipid-rich lymph into the peritoneal cavity It is a common complication seen following surgeries done for gynecological malignancies. Chyle leak following benign surgery is an extremely rare entity. The presence of a milky appearing ascitic fluid with triglyceride content above 200 mg/dl is diagnostic of chylous ascites. High-protein and low-fat diet with MCT reduce the production and flow of chyle and seal the leak. We present a 53-year-old, para 2 living 2, lady with heavy menstrual bleeding and congestive dysmenorrhea for 3 years. She was diagnosed with AUB A and failed to respond to medical management. Her general physical examination was unremarkable and gynaecological examination revealed bulky uterus enlarged to 12 weeks’ gravid uterine size. She underwent TLH and BSO. On post-operative day 2, 280 ml milky white fluid was noted in the pelvic drain. Drain fluid triglyceride was noted to be 723 mg/dl. High protein and low fat diet with MCT was initiated. Over the following 3 days the drain output showed a gradual decline and on day 6 serous fluid was noted in the drain. She recovered well and was discharged on 8th post-operative day. Chylous ascites following hysterectomy has not been reported in literature. We report this case to emphasize the rarity of this complication following laparoscopic hysterectomy for benign pathology and the successful management by conservative measures.